Does globalization restrict budgetary autonomy? A multidimensional approach - Friedrich Heinemann (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1999)
Does globalization restrict the leeway for national budgetary policy? With the help of cluster and discriminant analysis this study provides evidence on the basis of the experience of OECD countries since the 1970s. Four budgetary dimensions are included in the analysis: tax structure, expenditure structure, public debt and budget size. Globalization as a potential driving force for changes in government finance is identified in form of variables on the existence of capital and current account restrictions, on the exposure to international trade and the exchange rate regime. The results suggest that globalization does indeed matter for government budgets. However, substantial room for an individual national policy particularly in regard to expenditure structure and public debt is left.
Keywords: H87; H60; 330; Fiscal Policy; Tax Competition; Globalization; Cluster Analysis; Discriminant Analysis; Finanzpolitik; Globalisierung; Steuerwettbewerb; Clusteranalyse; OECD-Staaten